RESEÑA de : Bauer, Christoph J.; Caspers, Britta; Hebing, Niklas; Junng, Werner; Wendt Holger (Editores). Georg Lukács. Werk undWirkung. Duisburg, Alemania : Universitätsverlag Rhein-Ruhr, 2008 - Cubo Ugarte, Óscar (ENDOXA, 2010)
-